Analysis of genetic diversity and population structure in Argentine and Bolivian Creole cattle using five loci related to milk production - Lirón, Juan Pedro (2002)
Data from five protein-coding loci related to dairy production were used to study the genetic diversity and population structure of Argentine and Bolivian Creole cattle breeds. Genomic DNA was extracted from blood samples of six Creole cattle breeds: Argentine (n = 230), Patagonian (n = 25); "Saavedreño" (n = 140), "Chaqueño Boliviano" (n = 30), "Yacumeño" (n = 27), and "Chusco" (n = 11). κ-casein, β-lactoglobulin, growth hormone and prolactin were measured by PCR-RFLP, while αS1-casein was typed by PCR-ASO. The results are discussed, focusing on: historical origin, recent differentiation and selection events, Zebu gene introgression, and population structure. This work shows that: (i) For the studied genes, the observed gene frequency profiles of Argentine and Bolivian Creole cattle breeds were close to the data reported for Iberian breeds and for other South-American Creole cattle breeds which are historically related; (ii) although Zebu gene introgression has been reported at the studied loci, these breeds seem to be far from the Zebu gene frequency profiles; and (iii) the Argentine and Bolivian Creole cattle showed significant levels of subdivision, but each population has maintained its degree of genetic variability.